Growth and survival in Quercus ilex L. seedlings after irrigation and artificial shading on Mediterranean set-aside agricultural land - Rey Benayas, José M (Ann. For. Sci., 1998)
Considerable quantities of agricultural land are being transformed into forested lands in E.U. countries. To assess afforestation practice, we analyzed the growth and survival of 800 Quercus ilex sp. ballota seedlings in set-aside agricultural land under semi-arid Mediterranean climate conditions in central Spain. The survival and growth of the seedlings were monitored for 3 years after planting with an experimental design that included all four combinations of: i) irrigation or no irrigation during the dry season; and ii) artificial shading or no shading. Significant differences in survival and growth (height, stem diameter and crown projected area) were found among treatments. Survival was lowest (53 %) in the control plots, and very similar (around 93 %) for the irrigation, shade and combined treatments. Most of the mortality occurred after the first dry season. The high survival rate in irrigated but not shaded plots coincided with a thick layer of the weed Amaranthus retroflexus L. (in the first dry season). Seedling growth was greatest on average under irrigation and shade conditions. Shade was found to have a significant effect for all growth measurements, while irrigation alone only affected stem diameter growth and crown projected area in interaction with shade. Growth measurements were correlated to microclimatic conditions in the plots as measured by the amounts of water and actual evapotranspiration. We conclude that the attenuation of summer stress must be considered in the early stages of successful plantation practice of set-aside agricultural land in a dry environment.
Keywords: Agricultural land; Growth; irrigation; shade; Survival